Slowdown of Shirase Glacier, East Antarctica, caused by strengthening alongshore winds - Miles, Bertie W. J.; Stokes, Chris R.; Jenkins, Adrian; Jordan, Jim; Jamieson, Stewart S. R.; Gudmundsson, Hilmar (The Cryosphere, 2023)
Around large parts of West Antarctica and in Wilkes Land, East Antarctica, increased wind-forced intrusions of modified Circumpolar Deep Water (mCDW) onto the continental shelf have been associated with mass loss over the last few decades. Despite considerable seasonal variability, observations in 2018 have also confirmed relatively high basal melt rates of up to 16 m a−1 underneath the Shirase ice tongue in Enderby Land, East Antarctica. These high basal melt rates are also caused by intrusions of mCDW onto the continental shelf, but the catchment of Shirase Glacier has been gaining mass, a trend often attributed to increased precipitation. Here, we document the dynamical ocean-driven slowdown, ice surface thickening and grounding line advance of Shirase Glacier in response to strengthening easterly winds that reduce mCDW inflow and decrease basal melt rates. Our findings are significant because they demonstrate that warm ice shelf cavity regimes are not universally associated with glacier acceleration and mass loss in Antarctica, and they highlight the overlooked role of the impact of easterly winds in the recent mass gain of the Shirase Glacier catchment.